PERUBAHAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DARI PAJAK PUSAT MENJADI PAJAK DAERAH - Budi Ispriyarso (Faculty of Law, Universitas Diponegoro, 2011)
Duty of Acquisition Rights to Land and Building (BPHTB) is a tax imposed on the acquisition of land and or buildings. Its legal basis is the Act No. 21 of 1997 which was later amended by Act No. 20 of 2000. In its development under the provisions of Act No. 28 of 2009 on Local Taxes and Levies (PBOR). which was originally BPHTB change is the central tax became local taxes. The change of BPHTB of central taxes to local taxes is interesting to study, given that this change would have an impact also on its implementation